Pengetahuan Ibu Post Partum tentang Perawatan Luka Perineum dengan Pencegahan Infeksi: Post-Partum Mother's Knowledge of Perineal Wound Care with Infection Prevention - Misna, Rumini; Julita, Tria (Jurnal Bidan Cerdas, 2020)
Perineal care is the fulfillment of the need to nourish the thigh's area, which is restricted to the vulva and anus in mothers who are in the period between the birth of the placenta until the return of generative organs such as before pregnancy. According to the World Health Organization (WHO), in 2015, the world's Mother Mortality Rate reached 228/100,0000 live births. This study was to determine the relationship of postpartum maternal knowledge about the care of perineal wounds with infection prevention at the Siti Kholijah Hasibuan Clinic. The research used an analytic survey with approach Cross-Sectional. Sampling used a total population of 31 postpartum mothers who suffered the perineal injury. This study used primary data from the results of univariate and bivariate analysis data processing. Based on the statistical test, chi-square Î±=0.05 between knowledge of postpartum mothers, was obtained a p-value of 0.003 (p <0.05). The study concluded that there is a relationship between maternal knowledge postpartum care of wounds perineal and prevention of infection at the Siti Kholijah Hasibuan Clinic